Conciencia ambiental y prácticas de gestión de residuos sólidos en los pobladores de la zona baja de Belén, Iquitos 2024 - Valera Goncalvez, Alis Dagnith (2025)
This study, of a descriptive, analytical, correlational and transversal type, aims to analyze the relationship between the level of environmental awareness of the inhabitants of the lower area of Belén and their waste management practices, as well as their impact on the conservation of the water from the Itaya River. The sample was selected based on the commercial activity of Venecia, Itaya, Blasco Núñez and Santa Rosa streets, considering a total of 80 people who interact daily with environmental management in the area. A targeted intentional sampling was used and, for data collection, a survey was applied with a structured questionnaire of 23 items, whose Cronbach's Alpha coefficient of 0.703 indicates acceptable reliability. For the inferential analysis, the normality of the data was evaluated using the Kolmogorov Smirnov test, the results of which showed that both analyzed variables do not follow a normal distribution (p = 0.004 or p = 0.000). Consequently, Spearman's nonparametric test was used for correlation analysis. The main findings reveal that the majority of respondents have extensive knowledge about the pollution of the Itaya River and its effects on health and biodiversity. However, the predominant practices in homes include burning waste and its improper disposal in the river, which aggravates pollution. Although some respondents practice waste separation, this behavior is rare due to the lack of infrastructure and environmental education. Furthermore, socioeconomic factors, such as limited income and lack of adequate infrastructure, as well as cultural factors, such as traditions and beliefs, were identified as playing a determining role in waste management practices in the community.